An integrated modeling system for the estimation of motor vehicle emissions - Zachariadis, Theodoros; Samaras, Zissis (My University, 1999)
The paper provides a summary of accomplished and ongoing activities in the field of motor vehicle emission modeling in Europe. These activities have led to the development of a system of methods and corresponding computer models that address all the issues related to motor vehicle emissions that are of interest to policy-makers, institutions, and the automotive and oil industries. The Coordination of Information on Air Emissions/Computer Program to Calculate Emissions from Road Traffic (CORINAIR/COPERT) methodology for the estimation of emissions from road vehicles is presented and compared with other models. A COPERT-based approach for microscale traffic emission estimation, with direct application in regional and urban emission inventories, is outlined, and relevant case studies are briefly discussed. The FOREMOVE model, developed for forecasts of motor vehicle emissions, is presented, together with some results from its application in the European Auto/Oil program. Particular attention is given to modeling the deterioration of in-use vehicles. Finally, the major areas of further research in the field of vehicle emissions in Europe are indicated.
Keywords: Air pollution; Computer simulation; Environmental management; Environmental monitoring